PENYULUHAN PEMANFAATAN LIMBAH ORGANIK SEBAGAI BAHAN AMELIORAN UNTUK MENINGKATKAN PRODUKTIVITAS JAGUNG KETAN DI MUNCUK KARYA, AMPENAN - Astiko, Wahyu; Fauzi, Mohamad Taufik; Sudirman, Sudirman; Muthahanas, Irwan (Jurnal Abdi Insani, 2024)
Glutinous corn is popular due to its delicious taste, savory flavor, and soft texture, with a very high amylopectin content of up to 90%, which is beneficial for diabetics. Its popularity is increasing as an alternative food, such as corn porridge and instant corn rice. However, the productivity of glutinous corn in the "Karya Ushaha Bersama" farmer group remains low, around 2-2.5 tons per hectare. This activity aims to enhance farmers' understanding of utilizing organic waste as ameliorant materials to increase glutinous corn productivity. The methods used include lectures, discussions, Q&A sessions, demonstrations, and hands-on practice. The training also covers the use of organic materials such as compost, manure, and rice husk charcoal as ameliorants. The sessions were conducted smoothly and received active participation from the farmers. The results showed a significant increase in participants' understanding and skills regarding the production and use of ameliorants from organic waste. The use of a mixture of 50% cow manure and 50% mycorrhizal biofertilizer proved effective in improving the growth and yield of glutinous corn. This ameliorant also enhances the development of mycorrhiza in the soil and improves soil fertility. The use of a 50% cow manure and 50% mycorrhizal biofertilizer mixture is recommended to boost plant growth, yield, mycorrhiza development, and soil fertility. Increased productivity of glutinous corn is expected to improve the welfare of farmers in the area.